Inflammatory signaling pathways play a role in SYK inhibitor resistant AML - Sarah Tausch; Christina Villinger; Gabriela Alexe; Daniel J. Urban; Min Shen; Dominique Jahn; Jonas Vischedyk; Sebastian Scheich; Hubert Serve; Matthew D. Hall; Kimberly Stegmaier; Thomas Oellerich; et al. (Scientific Reports)
Abstract Trials have shown promising clinical activity of the selective SYK inhibitor entospletinib in patients with high expressing HOXA9/MEIS1 acute leukemias. As the development of resistance mechanisms is a common problem in the use of targeted drugs, we performed a chemical library screen to identify drug sensitivities in SYK inhibitor resistant AML cells. We identified that SYK inhibitor resistant cells displayed an increased sensitivity to glucocorticoids. Glucocorticoids are potent immunosuppressants which work in part by inhibiting the transcription of cytokine genes. RNA sequencing of entospletinib resistant cells revealed a strong enrichment of inflammatory response and TNFα signaling via NF-κB gene sets in comparison to naive cells. Naive AML cells treated with entospletinib showed a strong downregulation of the same gene sets which were upregulated in the resistant state. Our data suggest that inflammatory signaling pathways play a role in entospletinib resistant AML cells.